(untitled) (CIPEEX, 2025)
Introduction: Unconventional Food Plants (PANCs), are a diverse food alternative, rich in nutrients and bioactive compounds that modulate the intestinal microbiota and promote the body’s immune health. Given this, PANCs contain probiotic fibers that promote gastrointestinal balance through the presence of antioxidant and anti-inflammatory substances. However, there are still few studies addressing the active use of these foods, limiting people’s understanding and knowledge of this topic. Objective: To expand knowledge about PANCs in the field of health, exploring their impact on the intestinal microbiota and, consequently, on the immune system. Methodology: A literature review was conducted with studies collected from PubMed, SciElo, and Google Scholar, using the health sciences descriptors (DeCS): “Gastrointestinal Microbiome,” “Immune Response” and “Medicinal Plants”. Seven studies conducted between 2016 and 2021 were included, excluding abstracts and mini-reviews. Results: PANCs are rich in fiber, vitamins, minerals, and bioactive compounds that allow them to play an antioxidant, antimicrobial, antidiabetic, and anti-inflammatory role. Given this, they act positively in modulating the intestinal microbiota and increasing the bioavailability of nutrients, allowing for body weight control. In addition, PANCs play a crucial role in immune modulation, since a well-functioning digestive system maintains the integrity of the intestinal barrier, reducing toxin permeability and excessive activation of the innate immune system. This leads to lower production of pro-inflammatory cytokines, allowing anti-inflammatory action that improves the body’s metabolic activity. However, despite the benefits of these foods, there are insufficient studies on their nutritional potential and their uses for health promotion, limiting further exploration of the topic. Conclusion: PANCs have high nutritional and therapeutic value, contributing to health promotion through their beneficial effects on the regulation of the intestinal microbiota and anti-inflammatory action in the gastrointestinal tract. However, further studies are needed to explore this topic more fully and use it as a beneficial resource in the health system.